STRATEGI PEMASARAN DALAM MENINGKATKAN JUMLAH NASABAH PEMBIAYAAN MURABAHAH DI PT. BPRS AMANAH INSAN CITA - Tri Annisya; Ahmad Amin Dalimunhe; Haidar Helmi (Nurul Jadid University, 2022)
This research aims to analyse the marketing strategy BPRS Amanah Insan Cita implemented to increase the number of murabahah financing customers temporally. This study uses a descriptive analysis method with a qualitative approach. Data sources were obtained through interviews, documentation, observation, and journal references. The results of this study indicate that BPRS Amanah Insan Cita uses the 4P marketing mix strategy (location, product, price and promotion). The strategy more often used in this case is the promotion strategy, compared to the three methods. Through a promotional process, customers better understand the advantages and disadvantages of murabahah financing products. The promotion strategy is more effective and aimed at the general public to increase the number of customers faster.